Determining the 180-year Change of Cd, Fe, and Al Concentrations in the Air by Using Annual Rings of Corylus colurna L - Key, Kubra; Kulaç, Şemsettin; Koç, İsmail; Sevik, Hakan (Springer Science and Business Media LLC, 2022)
Heavy metals (HMs), among the components of air pollution that is one of the utmost critical concerns our world has faced, are one of the biggest threats to living organisms. The plants, as a biomonitor, offer the most effective solution in tracking the change of HM concentration on earth and taking them under control. This paper aimed to evaluate the differences in cadmium (Cd), iron (Fe), and aluminum (Al) concentrations by using the annual rings of a 180-year-old Corylus colurna L. tree, which was cut in late 2020. Moreover, HMs in outer and inner bark were also compared to the values found in wood, and the direction-based change in the concentrations of these HMs was examined. As a result, the concentrations statistically differed between wood and barks for all three elements only in the north side p < 0.001), and bark samples had higher Cd, Fe, and Al element concentrations than wood. When examining the annual rings, the highest values were commonly observed in the western and northern sides, and there were notable differences between the directions in the same term. The difference is thought to be the effects of highway and steel and iron facility located at the nearest point. In conclusion, the results showed that the use of the species and monitoring method employed in this study were very appropriate for tracking the variation in Cd, Fe, and Al concentrations, and these HMs have almost no transfer between organs and cells of the Corylus colurna.
Keywords: Heavy-Metal Accumulation; Tree-Rings; Traffic Density; Pine; Spectrometry; Elements; Plants; China; Pb; Aluminum; Annual Tree Ring; Cadmium; Iron; Turkish Hazelnut; 13. Climate action; 15. Life on land